2016
DOI: 10.1039/c6cy00558f
|View full text |Cite
|
Sign up to set email alerts
|

Extended study of ammonia conversion to N2 using a Ru/0.2TiZrO4 catalyst via catalytic wet air oxidation

Abstract: During the (NH4)2SO4 degradation, both the NO2− and NO3− generated can react with NH4+ in the solution and produce N2 as the only final product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Indeed, the formation of nitrogen from catalytic wet oxidation of ammonia on Ru/TiO 2 has been predominantly ascribed to a reaction in aqueous phase between NO 2 – /NO 3 – and NH 4 + according to steps and . Such steps have been further confirmed in slightly acidic conditions: As a matter of fact, it was recently found that step at the surface of the catalyst and the reaction between NO 2 – and NH 4 + to produce N 2 coexist, but this latter one becomes more predominant when pH decreases …”
Section: From Kinetics and Reaction Mechanisms To Reactor Design In C...mentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, the formation of nitrogen from catalytic wet oxidation of ammonia on Ru/TiO 2 has been predominantly ascribed to a reaction in aqueous phase between NO 2 – /NO 3 – and NH 4 + according to steps and . Such steps have been further confirmed in slightly acidic conditions: As a matter of fact, it was recently found that step at the surface of the catalyst and the reaction between NO 2 – and NH 4 + to produce N 2 coexist, but this latter one becomes more predominant when pH decreases …”
Section: From Kinetics and Reaction Mechanisms To Reactor Design In C...mentioning
confidence: 93%
“…In a last example, theoretical calculations based on the frontier molecular orbital theory clarified the controversies arising in the steps involved in the production of nitrogen in the catalytic wet oxidation of ammonia showing that the symmetry of the HOMO for NH 4 + matches with the LUMO of NO 2 – leading to the production of nitrogen …”
Section: From Kinetics and Reaction Mechanisms To Reactor Design In C...mentioning
confidence: 99%
“…m -Cresol is an important chemical raw material that is mainly used as a pesticide intermediate, such as insecticides fenitrothion, thiophosphate, tsumacide, and so forth. , However, little attention has been paid to the application of 3-D electrode technology to the degradation of pesticides. Moreover, m -Cresol is frequently found in industrial wastewater because of its extensive application, and therefore, it is considered as one of the primary pollutants in coal-chemical engineering wastewater …”
Section: Introductionmentioning
confidence: 99%